Money Demand and the Interest Rate Level - Harris, Elinor (Quarterly Journal of Economics, 1950)
I. Introduction, 105. — II. Conclusions, 107. — III. The period of pure monetary expansion, 109. — IV. Wartime rate stabilization, 113. — V. Downward break from the controlled pattern, 115. — VI. Debt reduction and re-introduction of rate uncertainty, 118. — VII. Use of controlled uncertainty, 120.